Proceedings of the 17th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Industry, Innovation 2019
DOI: 10.18687/laccei2019.1.1.24
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic factors on household solid waste (HSW) generation of the city of Guayaquil, Ecuador.

Abstract: This paper estimated the household solid waste (HSW) generation and composition in Guayaquil, Ecuador. The study also determined the socioeconomic factors influencing the waste generation of the households in the city by using Ordinary Least Square (OLS) regression. For this effect, a stratified random sampling methodology was used, resulting in the selection of 665 sample households for this study. The applied methodology resulted in a composition of HSW: organic waste (72,6%), plastic (8,7%), glass (2,4%), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…After in-depth review of online literature, little information showed to be available relating social factors with the generation of waste cooking oil. However, experience in previous research [1] mention that household size and social status always influence household waste. Other findings closely related to ours revealed: the necessity for rigorous public awareness campaign in order to encourage households to properly manage their WCO through recycling for biodiesel production [12] also, access to recycling facilities evidently has most impact on recycling behavior.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…After in-depth review of online literature, little information showed to be available relating social factors with the generation of waste cooking oil. However, experience in previous research [1] mention that household size and social status always influence household waste. Other findings closely related to ours revealed: the necessity for rigorous public awareness campaign in order to encourage households to properly manage their WCO through recycling for biodiesel production [12] also, access to recycling facilities evidently has most impact on recycling behavior.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In previous research, the authors identified how domestic solid waste generation varies according to certain socioeconomic factors [1] and determined the energy potential of such waste by theoretically characterizing the residues with the help of literature [2]. However, to our knowledge no research exists for liquid domestic waste produced in the city.…”
Section: Introductionmentioning
confidence: 99%
“…In the year 2016, Kolekar [9] reviewed these techniques and concluded that correlation and regression analysis is the commonly used approach for forecasting the SWGR. Moreover, Lakioti et al, Suthar et al, Trang et al and Hidalgo et al [10][11][12][13][14] proved that socio-demographic and economic parameters are the most influential parameters affecting the amount of solid waste generation amount.…”
Section: Introductionmentioning
confidence: 99%
“…Many reasons such as rapid population growth, urbanization, development of the economy, developments in science and technology, improvement in the living standards of society and people's lifestyles, and development of the mode of consumerism have led to a significant increase in the production of the municipal solid waste (MSW) and the diversity of its composition (Astane & Hajilo, 2017; Liu et al., 2019). Lately, solid waste management (SWM) has become a serious issue and major concern for many countries, especially for developing countries, and is now one of the urban environmental subjects discussed by the planners and policymakers (Ali & Siong, 2016; Hidalgo et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To plan a MSWM strategy for a specific city, it is substantial to know the amount and composition of the waste produced (Bandara et al., 2007; Hidalgo et al., 2019). The knowledge of the amount and composition of the solid waste produced is gained based on studies of classification of solid waste at the level of complexes or populated areas.…”
Section: Introductionmentioning
confidence: 99%